ABUNDANCE OF ZOOPLANKTON AND PHYSICO CHEMICAL PROPERTIES OF KAMAREDDY TOWN LAKE, TELANGANA - KUMAR, P. ANIL; BALAKRISHNA, D.; JANGIR, O. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
In the present investigation water physico-chemical [parameters (Atmospheric Temperature (AT), Water Temperature (WT), Transparency (Trans), pH, Total Dissolved Solids, Electrical Conductivity (EC), Dissolved Oxygen (DO), Free Carbon Dioxide (CO2), Total Alkalinity (TA), Total Hardness (TH), Chlorides (Cl), Phosphates (P) and Biological Oxygen Demand (BOD)) and four major of Zooplankton species (Rotifera, Copepoda, Cladocera and Ostracoda) were analyzed during the period of February 2018 to January 2019. The physico-chemical parameters were fall within the permissible limits of APHA, BIS. Temp. both ambient and water, Trans, pH, EC, DO, CO2 and TA values were highest recorded in summer season. The total dissolved solids results highest recorded in rainy season is due to blending of sediments in to the lake. A total of fifteen number of zooplankton species were observed, out of which eight species of Rotifers (Brachionus falcatus, Brachionus angularis, Brachionus caudatus, Lecane luna, Keratella tropica, Keratella cochlearis, Filinia longiseta and Cephalodella gibba), three species of Copepods (Masocyclops hylinus, Mesoscyclops leukarti and Paracyclops fimbriatus), three species of Cladocerans (Ceriodaphnia cornuta, Diaphanosoma sps and Moina macrocopa) and one species of Ostracod (Heterocypris) were observed. The dominance group was Rotifera and followed by Copepoda, Cladocera and Ostracoda, respectively.